Towards Inclusive Education: A Conceptual Model for Curriculum Management in Inclusive Schools - Kriswanto, Didi; Suyatno, Suyatno; Sukirman, Sukirman (Indonesian Journal of Education and Social Studies, 2024)
Providing access to learning in inclusive schools for children with special needs in Indonesia is still concerning. The implementation of the curriculum in inclusive schools has not been able to accommodate all Children with Special Needs. This study aimed to find a conceptual model of curriculum management as an alternative and practical approach to implementing inclusive schools. This study was conducted in one of the elementary schools in Yogyakarta using qualitative methods with case study. Data collection was carried out through observation, interviews, and documentation. Triangulation of sources, techniques, and time was used to test the validity of the data to test the validity of the data. Data analysis includes collection, reduction, presentation, and verification/conclusions. The study results indicate that inclusive curriculum management has been implemented and structured through planning, organizing, implementing, and evaluating/assessing, considering all aspects involved in the process. The results of this study can be used as a guideline for implementing curriculum management in inclusive schools. However, further research is needed on the effectiveness of implementing curriculum management in inclusive schools and a more in-depth study of the obstacles and challenges in implementing curriculum management in inclusive schools.